Meningkatan Keaktifan Belajar Siswsa Melalui Model Pembelajaran Problem Based Learning (PBL) Kelas IV FASE B Di SDN 16 Menawai Tekam - Diman Diman (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The purpose of this study is to improve student activeness and learning outcomes through the application of problem-based learning (PBL) learning models.The type of research used is PTK. The subject of research of students of grade IV. Data collection techniques use tests, observation data, activeness assessment rubrics. The data analysis techniques used are descriptive, quantitative and qualitative. The results of the study on learning activity in the precycle (64.87%) 10 inactive students in cycle I increased to (24.32%) 9 students were quite active and in cycle II increased to (83.78%) 14 students who were active. Meanwhile, precycle learning outcomes showed completeness of (41%) 10 students completed then increased in cycle 1 to (54%), 14 students completed and (81%) 14 students completed in cycle II. Thus, through the application of the problem-based learning (PBL) learning model, it can increase the activeness and learning outcomes of grade IV students of SDN 16 Menawai Tekam.